2009
DOI: 10.1089/ees.2008.0231
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Activated Carbon as a Reactive Cap Sorbent for Sequestration of Polychlorinated Biphenyls in the Presence of Humic Acid

Abstract: This study investigated the interferences caused by high humic acid concentrations on the adsorption of coplanar and noncoplanar polychlorinated biphenyls (PCBs) on coconut shell activated carbon. In particular, the research focuses on the application of activated carbon as a reactive cap for contaminated sediment sites, a possible intervention to reduce contaminant flux through pore water, and to organisms in aquatic environments. Kinetic and equilibrium studies were conducted using activated carbon as a sorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Carbonaceous geosorbents and synthetic activated carbon (AC) have a much stronger adsorption affinity for organic contaminants, in particular at low solute concentrations than amorphous organic carbon (e.g., humic substances). Numerous studies have demonstrated the efficiency of AC to reduce the bioavailability of organic pollutants, such as polychlorinated biphenyls (PCBs) (McLeod et al, 2008; Sharma et al, 2009), dichlorodiphenyltrichloroethane (DDT) (Tomaszewski et al, 2008), and polycyclic aromatic hydrocarbons (Cornelissen et al, 2006), in aquatic environments. Treatments of freshwater sediments with 2.5% AC reduced PCB concentrations by more than 97% in water (McLeod et al, 2008).…”
mentioning
confidence: 99%
“…Carbonaceous geosorbents and synthetic activated carbon (AC) have a much stronger adsorption affinity for organic contaminants, in particular at low solute concentrations than amorphous organic carbon (e.g., humic substances). Numerous studies have demonstrated the efficiency of AC to reduce the bioavailability of organic pollutants, such as polychlorinated biphenyls (PCBs) (McLeod et al, 2008; Sharma et al, 2009), dichlorodiphenyltrichloroethane (DDT) (Tomaszewski et al, 2008), and polycyclic aromatic hydrocarbons (Cornelissen et al, 2006), in aquatic environments. Treatments of freshwater sediments with 2.5% AC reduced PCB concentrations by more than 97% in water (McLeod et al, 2008).…”
mentioning
confidence: 99%
“…However, in most cases it is necessary to use series of batch adsorption experiments over the desired range of equilibrium concentrations to determine the Freundlich (or other model) parameters. These experiments have illustrated the effects of competition with other contaminants and the potential for fouling with natural organic matter or with biofilms (McDonough et al, 2008;Sharma et al, 2009). In general, it appears that the effect of such competition may be to reduce the sorption capacity of activated carbon approximately an order of magnitude.…”
Section: Organic Compounds Sorption To Sediments and Capping Materialsmentioning
confidence: 99%
“…Thus, a 1-cm layer of activated carbon layer has potentially the equivalent breakthrough time of a 50 meter (m) layer of sediment with an f oc of 1% or 500 m of sand with an effective f oc of 0.1%. Activated carbon exhibits two significant limitations in applications as a contaminated sediment cap: a tendency for fouling by NAPL or natural organic matter (DOC) that will reduce the sorptive capacity (Sharma et al, 2009) and a difficulty in placing the carbon in water due to its low density. The wet density of activated carbon is only slightly greater than that of water, and so the carbon can settle and be retained at the sediment-water interface although the potential for resuspension and erosion is substantially greater than soil or sediment grains of a similar diameter.…”
Section: Activated Carbonmentioning
confidence: 99%
“…Specifically, organic constituent modeling was performed to evaluate the performance of the granular activated carbon (GAC) treatment layer for adsorption of C10–C12 aliphatic hydrocarbons, which were used as representative for all TPH‐DRO measured during the Portland Harbor remedial investigation. For this application coal‐based, GAC was selected because hydrophobic organic contaminants such as PAHs are large molecular structures that require suitable pore size for sorption and encounter interferences due to pore blockage and competitive sorption in the presence of natural organic matter present in the sediment (Amstaetter, Eek, & Cornelissen, 2012; Sharma, Gardner, Melton, Hawkins, & Tracey, 2009).…”
Section: Cap Designmentioning
confidence: 99%